2 - Enjeux économiques, conflits africains et relations internationales: 10.4314/ad.v24i3.22125 - Mamadou Koulibaly (Africa Development, 1999)
Dealing with conflicts in Africa as a problematic, this paper outlines four characteristics of conflicts in Africa: 1) that all African conflicts have economic stakes that are more or less obvious; 2) that all African conflicts are influenced by international and domestic geopolitics; 3) that African conflicts can be explained by political, economic and socio-cultural variables; and finally, that African conflicts are brought about by ill-organised, non free and fair elections.